The Israeli Occupation and the Struggle for an Independent Palestine - Maram, Ahmad Nabilul; Fikri, Syarifuddin Ala Dzil; Hikami, Abdullah Faqih (Yayasan Pesantren Mahasiswa An-Nur, 2024)
This research explores the historical foundations and development of the Zionist movement, emphasizing the involvement of European colonial powers in advancing its goals and the subsequent emergence of Palestinian nationalism as a counterforce. Employing a qualitative methodology that includes historical analysis and a comprehensive literature review, the study investigates the repercussions of Zionism on Palestinian society, the national resistance against the Zionist settler-colonial initiative, and the dominant efforts to marginalize Palestinian historical narratives. The findings reveal that the establishment of the State of Israel in 1948, facilitated by colonial support, served as a pivotal moment in the Zionist agenda. Strategic errors by Arab nations and Palestinian leadership contributed to a weakened campaign for Palestinian independence. Despite these challenges, Palestinians have demonstrated remarkable resilience in maintaining their identity and asserting their rights. The study concludes that achieving lasting peace necessitates confronting historical injustices, safeguarding human rights, and promoting equitable and honest dialogue between the parties involved. It underscores the imperative for international assistance in formulating a just and comprehensive resolution. Furthermore, the research highlights the significance of drawing lessons from historical complexities to foster a more equitable and peaceful future in Palestine.